The Impact of Diet on the Course of Seborrheic Dermatitis: A Narrative Review - Gruba, Martyna; Kantor, Berenika; Grzywacz-Guza, Aleksandra; Hatala, Patrycja; Lewczuk, Aleksandra (Quality in Sport, 2026)
Seborrheic dermatitis (SD) is a chronic, recurrent inflammatory skin condition whose pathogenesis is associated with, among other factors, disturbances in the skin microbiome, overgrowth of Malassezia fungi, skin barrier dysfunction, and an abnormal immune response. The condition affects approximately 5% of the population and significantly impacts patients’ quality of life. The aim of this study was to analyze the available scientific data on the impact of daily diet on the course of seborrheic dermatitis and to identify foods that may alleviate or exacerbate the symptoms of the disease. A literature review covering the years 2016–2026 was conducted using the PubMed, Google Scholar, and Medline databases. The analysis included original articles, review articles, systematic reviews, and case reports concerning the relationship between diet and the course of seborrheic dermatitis. Available studies indicate that diet may influence the severity of skin lesions. A diet rich in fruits and vegetables has been shown to have a beneficial effect. In contrast, the consumption of alcohol, highly processed foods, sweets, fried foods, and spicy foods has been linked to a higher frequency or greater severity of symptoms. In summary, a well-balanced diet can play a significant role in supporting the treatment of seborrheic dermatitis and can help reduce the number of flare-ups and improve patients’ quality of life. Given the limited number of studies and the inconclusive results, further research is needed to develop detailed dietary recommendations for people with seborrheic dermatitis.